Optimization for detecting the efficiency of viral-vectored gene delivery via intratumoural route in murine model - Mustafa, Nor Hidayah (2015)
The journey of cancer and its therapy involve a committed process of discoveries either at preclinical set-up or clinical trials. The attractive features of viral-vectored therapy have shown significant progress at the level of animal models. Efficacy of the preclinical outcome eventually determines the successful rate of clinical endpoints. This study was conducted in order to evaluate the response of the replicative-incompetent-retroviral-based VP3 (rRV-VP3) treatment towards TROP-2 and CRIPTO-1 tumour markers in tumour modelling of Balb/c mice for seven subsequent days. TROP-2 and CRIPTO-1 were among the tumour markers involve in human tumour development while thorough investigation in murine model was still underway. The recovered rRV-VP3 particles produced 1.67 x 104 CFU/ml titer from Colony-Formation-Assay. The rRV-VP3 titer was then correlated with a standard curve generated from Real-Time PCR assay, giving the ratio of rRV-VP3 particles-to-infectious particles at 1:6.0 x 1010 in order to initiate virus transduction. Gene expression of TROP-2 and CRIPTO-1 were detected in both rRV-VP3 treated tumour-bearing murine model and the control group. Expression of VP3 protein can be detected only in rRV-VP3-treated group. The main causes of over expression of tumour markers could be due to the introduction of the xeno-therapeutic gene and the short half-life of rRV-VP3 particles. Since gene expression study through conventional RT-PCR assay was merely a tool to detect the effectiveness of VP3 delivery in vivo, additional sensitive confirmation of protein behaviour was done. Therefore, optimization for protein-protein interaction and expression was investigated using Biacore Surface-Plasmon-Resonance (SPR) assay as it could mimic the in vivo system while minimizing animal usage for in vivo work. Optimization of the ligands in the flow cells of the CM5 Sensor Chip was successful using 10 mM of sodium acetate of pH 5.0. Ligands were critical in detecting the presence of tumour markers and VP3 protein effectively. Eventually, the combination of 50mM NaOH and 10 mM glycine of pH 2.0 was the best regeneration buffer to disrupt the antigen-antibody complex. In vivo observation of rRV-VP3-treated group for seven consecutive days revealed dramatic VP3 protein expression especially in Day 2 and Day 5, hence implies the efficient transduction of gene in the tumour. However, TROP-2 expression was almost similar to VP3 expression (p>0.05). One plausible explanation of the similarity is the shortage of VP3 protein to associate with anaphase-promoting complex in G2/M phase of cell cycle and subsequently unable to sufficiently inhibit the tumour cells proliferation, thus allowing the continuous expression of TROP-2 during the mitosis stage. Contrarily, a minimal expression of VP3 in tumour cells down regulated the expression of CRIPTO-1 protein (p<0.05) and this could relate to VP3 involvement in interfering the CRIPTO-1/ mitogen-activated-protein-kinase (MAPK) signaling pathway. Unlike the rRV-VP3-treated group, the control untreated groups showed insignificant changes in the pattern of protein expressions (p>0.05). In summary, the usage of antibodies as the immobilized ligands for SPR was proven to be optimal for detecting tumour marker responses against VP3 treatment in in vivo analysis (p<0.05). In comparison to SDS-PAGE, the optimized SPR analysis managed to track the traces of protein expressions throughout the seven days of observation, enabling the interpretation of treatment analysis via real-time protein behavioural pattern.